Harga, Kualitas Layanan, dan Kepercayaan pada Transportasi Online Maxim terhadap Kepuasan Pelanggan - Sahda, Fatimah Talitha; Putri, Anisa Rachma; Kurniaty, Dewi (Research and Strategic Studies Center (Pusat Riset dan Kajian Strategis) Fakultas Syariah IAI Nasional Laa Roiba, 2024)
This research was conducted to see the effect of price, service quality, and trust on Maxim online transportation customer satisfaction in Jabodetabek. The method used in this research was a quantitative method using multiple regression analysis to measure the effect of one variable on another, and obtained a total of 150 respondents. This research uses two variables, namely the independent variable with the indicator variables Price, Service Quality and Trust. As well as the dependent variable, namely the Customer Satisfaction variable. Based on the results of a simple correlation analysis, a correlation of 0.489 was obtained, which means there is a positive influence between the variables because the R value is positive. Then based on the results of the overall index of Price, Service Quality and Trust, customer satisfaction was 48.9%, which shows a very strong relationship. Looking at the background of this research, Maxim customers are dissatisfied with several service indicators provided, therefore the practical implication of the results of this research that can be carried out by online transportation service providers Maxim is the need to provide service quality that is comparable to several things, such as Maxim drivers responding and implementing suggestions for complaints given by customers, maintaining customer trust so that customers can feel satisfied with the services provided, accompanied by drivers who always maintain cleanliness and tidiness so that customers can feel comfortable when using Maxim's online transportation services.